2020
DOI: 10.21203/rs.3.rs-26804/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated plasma Sirtuin2 level predicts heart failure after acute myocardial infarction

Abstract: Background and Objectives: There is currently no evidence regarding the role of plasma Sirtuin2 (SIRT2) level in heart failure after acute myocardial infarction (AMI) yet. This study assessed the relationship between plasma SIRT2 level and AMI, and also investigated the association of plasma SIRT2 level with major adverse cardiovascular events (MACE) and heart failure after AMI. Methods and Results: A total of 129 AMI patients were included in the present study. The major adverse cardiovascular events (MACE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This indicates that the level of SIRT2 is closely related to AMI, and AMI can be used to predict major adverse cardiovascular events (MACE) after AMI. 34 Another study conducted on AMI patients also found that mutations in the SIRT2 gene promoter are closely related to AMI. 35 Reperfusion can provide oxygen and nutrition, meanwhile remove toxic substances produced by necrotic cells to restore the ischaemic and hypoxic state of myocardial cells.…”
Section: Sirt2 and Myocardial Ischaemiareperfusion Injurymentioning
confidence: 98%
“…This indicates that the level of SIRT2 is closely related to AMI, and AMI can be used to predict major adverse cardiovascular events (MACE) after AMI. 34 Another study conducted on AMI patients also found that mutations in the SIRT2 gene promoter are closely related to AMI. 35 Reperfusion can provide oxygen and nutrition, meanwhile remove toxic substances produced by necrotic cells to restore the ischaemic and hypoxic state of myocardial cells.…”
Section: Sirt2 and Myocardial Ischaemiareperfusion Injurymentioning
confidence: 98%